Devising and Evaluating B2B Conceptual Model for B2B Portal for Mobile Interactive Devices Using Man Whitney U Test - Majlinda Fetaji; Labinot Morina; Bekim Fetaji; Mirlinda Ebibi (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
The focus of this research study is set in devising and evaluating the efficiency of B2B conceptual model for mobile interactive devices using Man Whitney U test which is a non-parametric test. As the case of this study is chosen creating a B2B model as an idea of linking businesses in region of Balkan. The system works on multiple languages. There are many businesses in the Balkans which have many problem in communication, and finding a market to sell their products which makes it hard to function and survive in business world. Many of these people use interactive devices 60-70% percent of the time compare with computers. The research focus was set to investigate and asses' main factors which help developers to develop a system which is compatible and easy to use. This research study tries to contribute with the devised B2B conceptual model that is intended to help developers in designing and developing a web portal for mobile devices. Through the Case Study investigated several impacting factors. Also evaluated the usability and user-friendliness of the developed B2B model and used Man Whitney U test to determine the impact. Insights and recommendations are provided.
Keywords: A11; 330; B2B business to business; B2B conceptual model; Man Whitney U test; web portal for mobile devices